2021
DOI: 10.3389/fimmu.2021.664109
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cells Are the Intriguing Players in the Puzzle of Idiopathic Pulmonary Fibrosis Pathogenesis

Abstract: Idiopathic pulmonary fibrosis (IPF) is the most devastating progressive interstitial lung disease that remains refractory to treatment. Pathogenesis of IPF relies on the aberrant cross-talk between injured alveolar cells and myofibroblasts, which ultimately leads to an aberrant fibrous reaction. The contribution of the immune system to IPF remains not fully explored. Recent evidence suggests that both innate and adaptive immune responses may participate in the fibrotic process. Dendritic cells (DCs) are the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 85 publications
1
10
0
Order By: Relevance
“…We found prognostic significance of DNA methylation expression levels in cg01043729 from ELAVL1 and cg06720244 from ZC3H13. In our study, neutrophil, CD4+ T cell and dendritic cells were significantly affected by the CNV of DEMGs in both LUAD and LUSC, which proved that neutrophil, dendritic cell and CD4+ T cell were more sensitive in the immune microenvironment of LUAD and LUSC, in keeping with other researches [ 50 ]. Besides, our results suggested that mutation of m6A-related genes had little correlation with immune cells in both LUAD and LUSC patients, which may because of the limitation of samples.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…We found prognostic significance of DNA methylation expression levels in cg01043729 from ELAVL1 and cg06720244 from ZC3H13. In our study, neutrophil, CD4+ T cell and dendritic cells were significantly affected by the CNV of DEMGs in both LUAD and LUSC, which proved that neutrophil, dendritic cell and CD4+ T cell were more sensitive in the immune microenvironment of LUAD and LUSC, in keeping with other researches [ 50 ]. Besides, our results suggested that mutation of m6A-related genes had little correlation with immune cells in both LUAD and LUSC patients, which may because of the limitation of samples.…”
Section: Discussionsupporting
confidence: 90%
“…Previous study [ 49 ] indicated that the infiltration of B Cell and the formation of tertiary lymphoid structures were positively correlated with the response to immunotherapy, which is in keeping with our findings. Dendritic cell is the most powerful APC (Antigen presenting cell), which could stimulate the proliferation of naive T cell, leading to kill tumors, and have a positive correlation with overall survival [ 50 ]. However, our finding was opposite to previous studies, which may due to individual differences.…”
Section: Discussionmentioning
confidence: 99%
“…Cells from the innate and adaptive immune systems, like mesenchymal stem/stromal cells (MSCs), Tregs, regulatory B cells, macrophages, dendritic cells, myeloid-derived suppressor cells and T-follicular helper cells have been associated with the pathogenesis of IPF, though the research in the area has often yielded conflicting results [ 168 , 169 , 170 , 171 , 172 ]. Even though IPF has been characterised as a fibrotic disease involving epithelial cell activation, as stated before, proinflammatory mediators like IL-1β, interleukin-6 (IL-6) and tumour necrosis factor-alpha (TNF-α) are involved in the onset as well as the progression of pulmonary fibrosis [ 173 , 174 , 175 ].…”
Section: Events In Ipf Hdacs Tgf-β Signalling and Therapeuticsmentioning
confidence: 99%
“…Dendritic cells are known to play a critical role in inflammation-driven fibrosis in multiple organs (Rahman and Aloman, 2013;Bocchino et al, 2021). Ahadome et al (2016) showed that classical DC contributed to ocular mucosal fibrosis through the retinoic acid pathway in a model of allergic eye disease.…”
Section: Dendritic Cellsmentioning
confidence: 99%